2014
DOI: 10.1002/lary.24384
|View full text |Cite
|
Sign up to set email alerts
|

Basaloid squamous cell carcinoma of the oral cavity: An analysis of 92 cases

Abstract: 2b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 15 publications
6
17
2
Order By: Relevance
“…The present literature review based on 119 oral BSCCs revealed essentially similar overall presentation as previously reported and could be considered as a tumor of old age occurring predominantly in men and showing a predilection to the tongue and floor of the mouth (Table 2) [17]. Furthermore, it could also be characterized as a tumor showing an aggressive clinical course, with approximately half of the patients developing local metastasis and slightly more than half the patients dying of the disease (Table 2).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The present literature review based on 119 oral BSCCs revealed essentially similar overall presentation as previously reported and could be considered as a tumor of old age occurring predominantly in men and showing a predilection to the tongue and floor of the mouth (Table 2) [17]. Furthermore, it could also be characterized as a tumor showing an aggressive clinical course, with approximately half of the patients developing local metastasis and slightly more than half the patients dying of the disease (Table 2).…”
Section: Discussionsupporting
confidence: 75%
“…Separating purely oral cavity BSCCs from oropharyngeal tumors was also problematic because lesions occurring at the base of the tongue and palate were considered as belonging to the oropharynx by some, whereas others have included these tumors as arising from the oral cavity [32,33]. However, subsequently, a review article based on 92 cases of purely oral BSCCs was also identified [17]. Most findings of this study corresponded with the findings of the present study, except for the commonest site of occurrence.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Prognostically, it is important to distinguish between BCC and BSC.In majority of cases, BSC has been diagnosed on biopsy and histopathological features have been discussed in detail. [1][2][3][4][5] The cytological features have not been discussed much before. To the best of our knowledge, this is the first case report discussing the characteristic cytological features of this rare entity.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological features of this rare entity have been well discussed in literature. [1][2][3][4][5] But there is scarcity of information on the cytological features of BSC. We have not come across a single case in literature discussing the cytological features of BSC.To the best of our knowledge, this is the first case report discussing the characteristic cytological features of BSC which helped us to clinch the diagnosis.…”
Section: Introductionmentioning
confidence: 99%